Parent to parent : information and inspiration for parents dealing with autism and Asperger's Syndrome - Boushey, Ann, 1957- (Jessica Kingsley Publishers, 2004)
When a child is diagnosed with autism or Asperger's Syndrome, what a parent needs most is information and inspiration. After her son Jon was diagnosed with high-functioning autism in kindergarten, Ann Boush+℗Ơy soon learned that, for her, knowledge was the key to peace. Written out of her own experience, this inspirational book provides the information that will empower other parents who find themselves in her situation, and inspire them in their quest for the right diagnosis and the right help for their child. With a good dose of humor, she encourages parents in the day-to-day challenges they.